Influência da suplementação de alecrim (Rosmarinus oficinallis L.) na ração sobre a remodelação cardíaca em ratos submetidos ao infarto do miocádio - Rafacho, Bruna Paola Murino [UNESP] (2015)
Cardiac remodeling plays a key role in post-infarction ventricular dysfunction. Some mechanisms, such as oxidative stress, inflammation and fibrosis can modulate this process. Thus, prevention of post-myocardial damage has great clinical relevance. In this context, there is great interest in natural products with antioxidant properties, as Rosemary leaves. Objective: To analyze the influence of the consumption of dried rosemary leaves in the chow on cardiac remodeling after myocardial infarction (MI) in rats. Methods: Male Wistar rats with 200-250 g were divided into 6 groups: 1) Sham group fed standard chow and not subjected to MI (SA0, n = 23); 2) Sham group fed standard chow supplemented with 0.02% rosemary and not subjected to MI (SA1, n = 23); 3) Sham group fed standard chow supplemented with 0.2% rosemary and not subjected to MI (SA2, n = 22); 4) group submitted to MI and fed standard chow (IA0, n = 13); 5) group submitted to MI and fed standard chow supplemented with 0.02% rosemary (IA1, n = 8); 6) group submitted to MI and fed standard chow supplemented with 0.2% rosemary (IA2, n = 9). After three months, systolic pressure, echocardiography and euthanasia for collection of biological material were performed. Left ventricular samples were evaluated: fibrosis (collagen, metalloprotease [MMP]-2 and TIMP- 1), inflammation (TNF-α, IFN-α, IL-10 and ICAM-1), cell death (Bcl-2 and caspase-3), energy metabolism (activity of lactate dehydrogenase [LDH], pyruvate dehydrogenase [PIDH], citrate synthase [CS], β-hydroxyacyl-coenzyme A dehydrogenase [β-CoA-OH-DH], Complex I and II of the respiratory chain of electrons and ATP synthase) and oxidative stress (activity of superoxide dismutase [SOD], catalase and glutathione peroxidase [GSH-Px] and lipid hydroperoxide concentration [LH], and Nrf-2, hemeoxigenase-1 [HO-1] and GSH-Px expression,). The values are presented as mean ± SEM and comparisons were made by two-way ANOVA, with ...